Juan Valverde de Amusco: Pioneering the Transfer of Post-Vesalian Anatomy - Luis-Alfonso; Concepción Reblet; José Luis Bueno-López (MDPI AG, 2023)
This article delves into the life and accomplishments of Juan Valverde de Amusco (c. 1525-c. 1587), a Spanish anatomist. Specifically, it focuses on his book titled HISTORIA de la composición del cuerpo humano. The book was the first anatomy opus published after Andreas Vesalius' De humani corporis fabrica libri septem, written in a Romance language, the Castilian Spanish language, making it the most renowned post-Vesalian anatomy book in Europe and beyond during the 16th and 17th centuries. Compiling complete editions and reproductions of figures, it had 19 editions and several translations. One of its principal contributions was the initial graphical representation of the stapes ossicle. It provided the first accurate description of the pulmonary circulation, vomer bone, and four extraocular rectus muscles. Throughout the book, Valverde corrected numerous of Vesalius' anatomical observations. HISTORIA de la composición del cuerpo humano was the first anatomy book to use chalcographic illustrations, which are of superior anatomical quality than those printed from engraved wood in Andreas Vesalius' book. Next, many anatomy textbooks of that time incorporated Valverde's book illustrations. Valverde's book was practical, timely, and well referenced, making it a valuable resource for scholars and non-scholars. The conclusion is that Juan Valverde de Amusco merits a place as a pioneer in scientific knowledge transfer.